Arabic Language Learning Curriculum Islamic Boarding School System - Adtman Adjun Hasan (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2020)
This article aims to find out about the Arabic language curriculum development model at Madrasah Aliyah Al-Falah Gorontalo. This research uses the type of field research or field research. The research method is descriptive qualitative, namely research on the Arabic language learning curriculum's description with the boarding school system at MA al-Falah Gorontalo. The results of this study explain that: curriculum development at Madrasah Aliyah al-Falah Gorontalo is based on several foundations, namely juridical, psychological, and sociolinguistic foundations. Meanwhile, the curriculum development model used in Madrasah Aliyah al-Falah Gorontalo has been analyzed using an administrative model and a grassroots model. The characteristics of learning Arabic in the boarding school system at Madrasah Aliyah Al-Falah are different from learning in other schools. What distinguishes this Madrasah from other schools in the curriculum used and uses the Islamic boarding school system. So that learning Arabic is not only taught in schools but also trained in dormitories.